Odpowiedzi

2010-01-05T17:55:17+01:00
Zad;14
a) 2(x+3) =10
2x+6 = 10
2x = 4/ :2
x = 2

b) 3(x-1)+2=8
3x-3 +2 = 8
3x = 9 / :3
x = 3

c) 2(13-x) - 9 = 1
26 - 2x -9 = 1
-2x = -16 / :(-2)
x = 8

d) 3(1-x)+2= -7
3 - 3x +2 = -7
-3x = -12 / :(-3)
x =4

e) 3(x+3)= 2(x+4) +x+1
3x+9 = 2x +8 +x +1
0 = 0

f) 4(3x+2) + 5(2x+2) = -(2x+13)
12x +8 +10x +10 = -2x -13
20x = -31 / : 20
x = 1,55

g) 4(x-2)-2(x-4) = 5(x+)- 3x
4x -8 -2x +8 = 5x - 3x
0 = 0

h)2(x-4)=2(x-1)+6(x+1)
2x -8 = 2x -2 +6x +6
-6x = 12 / : (-6)
x = -2

:)
2010-01-05T17:58:33+01:00
2(x+3) =10
2x + 6 = 10
2x = 10 - 6
2x = 4 / :2
x = 2

3(x-1)+2=8
3x - 3 + 2 = 8
3x = 8 + 3 - 2
3x = 9 /:3
x = 3

2(13-x) - 9 = 1
26 - 2x - 9 =1
-2x = 1 - 26 + 9
-2x = -16 /:(-2)
x = 8

3(1-x)+2= -7
3 - 3x + 2 = -7
-3x = -7 -3 - 2
-3x = -12 /:(-3)
x = 4

3(x+3)= 2(x+4) +x+1
3x + 9 = 2x + 8 + x +1
3x - 2x - x = 1 - 9 + 8
0 = 0
układ nieoznaczony, rozwiązaniem może być każda liczba rzeczywista

4(3x+2) + 5(2x+2) = -(2x+13)
12x + 8 + 10x + 10 = -2x -13
12x + 10x +2x = -13 - 8 - 10
24x = -31 / :24
x = -31/21
x= -1 10/21

4(x-2)-2(x-4) = 5(x+)- 3x
4x - 8 - 2x + 8 = 5x - 3x
4x - 2x - 3x - 5x =8-8
-6x = 0 /: (-6)
x = 0

2(x-4)=2(x-1)+6(x+1)
2x - 8 = 2x - 2 + 6x + 6
2x - 2x - 6x = 8 + 6 -2
-6x = 12 / (-6)
x = -2
2010-01-05T18:00:32+01:00
A) 2(x+3) =10
2x+6=10
2x=10-6
2x=4/:2
x=2

b) 3(x-1)+2=8
3x-3+2=8
3x=8+3-2
3x=9/:3
x=3

c) 2(13-x) - 9 = 1
26-2x-9=1
-2x=1-26+9
-2x=-16/:(-2)
x=8

d) 3(1-x)+2= -7
3-3x+2=7
-3x=-7-3-2
-3x=-12/:(-3)
x=4

e) 3(x+3)= 2(x+4) +x+1
3x+9=2x+8+x+1
3x-3x=9-9
0=0

f) 4(3x+2) + 5(2x+2) = -(2x+13)
12x+8+10x+10=-2x-13
22x+18=-2x-13
22x+2x=-18-13
24x=-31/:24
x=-31/24 (w ułamku)

g) 4(x-2)-2(x-4) = 5(x+)- 3x
4x-8-2x+8=5x-3x
2x=2x
2x-2x=0
0=0

h)2(x-4)=2(x-1)+6(x+1)
2x-8=2x-2+6x+6
2x-2x-6x=8-2+6
-6x=12/:(-6)
x=-2